AKUISISI TEKNOLOGI EKSTERNAL DAN KINERJA PERUSAHAAN - Widya Laila; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2019)
In the business world, technology owned by a company is an infrastructure that is very important in supporting the company's efforts to increase profits. The current global business trend is encouraging company managers to move away from the trend of building their own technology needed to become a trend to get technology through collaboration with other companies because it can reduce expensive research costs, stimulate the innovation process to be able to fulfill requests that will ultimately improve the performance produced. his study proposes a model that can be used to analyze the contribution of external technology acquisition to company performance External technology acquisition contributes positively to company performance, and this contribution is strengthened by the moderator effect of internal R & D effort. Investment in internal R & D effort does not only stimulate the occurrence of innovation processes that will be needed to produce good performance but also strengthen the company's absorptive capacity. Absorptive capacity is needed to strengthen the company's ability to learn the latest knowledge and technology